Usability Analysis of an Electronic Immunization Monitoring and Logistics System using PIECES and SUS - Citra Yustitya Gobel; Misrawati Aprilyana Puspa; Syarifah Fitrah Ramadhani; Siti Andini Utiarahman; Sinta Suleman (Universitas Islam Indragiri, 2026)
The Electronic Immunization Monitoring and Logistics System (SMILE) is an information system designed to support the integrated management of immunization records and healthcare logistics. The successful implementation of such a system depends not only on its functionality but also on its usability, which significantly influences user satisfaction and acceptance. This study aims to evaluate the usability of the SMILE application using the PIECES framework—covering Performance, Information, Economy, Control, Efficiency, and Service—and the System Usability Scale (SUS). A descriptive quantitative approach was employed, with data collected through observations, a literature review, and questionnaire surveys administered to 56 users of the SMILE application at the Gorontalo Provincial Health Office. The results of the PIECES analysis indicate that all evaluation dimensions achieved the